2022
DOI: 10.1007/s40820-022-00882-w
|View full text |Cite
|
Sign up to set email alerts
|

Highly Thermally Conductive Polymer/Graphene Composites with Rapid Room-Temperature Self-Healing Capacity

Abstract: Composites that can rapidly self-healing their structure and function at room temperature have broad application prospects. However, in view of the complexity of composite structure and composition, its self-heal is facing challenges. In this article, supramolecular effect is proposed to repair the multistage structure, mechanical and thermal properties of composite materials. A stiff and tough supramolecular frameworks of 2-[[(butylamino)carbonyl]oxy]ethyl ester (PBA)–polydimethylsiloxane (PDMS) were establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Yu et al used an elastic polyimide copolymer cross-linked by flexible and rigid segments to fill the gaps of a forest of vertically aligned carbon nanotubes, reaching a high thermal conductivity of 10.83 and exhibiting good self-healability. Additionally, similar excellent results can be obtained in the PBA–PDMS/graphene system . Moreover, in Ruan’s work, polyethylene glycol trimethylnonyl ether was used to perform liquid crystalline modification on graphene fluoride to achieve an ordered alignment.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Yu et al used an elastic polyimide copolymer cross-linked by flexible and rigid segments to fill the gaps of a forest of vertically aligned carbon nanotubes, reaching a high thermal conductivity of 10.83 and exhibiting good self-healability. Additionally, similar excellent results can be obtained in the PBA–PDMS/graphene system . Moreover, in Ruan’s work, polyethylene glycol trimethylnonyl ether was used to perform liquid crystalline modification on graphene fluoride to achieve an ordered alignment.…”
Section: Introductionmentioning
confidence: 60%
“…Additionally, similar excellent results can be obtained in the PBA−PDMS/graphene system. 30 Moreover, in Ruan's work, 31 polyethylene glycol trimethylnonyl ether was used to perform liquid crystalline modification on graphene fluoride to achieve an ordered alignment. The novel method achieves a high thermal conductivity of 4.21 W•m −1 •K −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38] Aligning anisotropic filler in one specific direction, for instance, the in-plane or vertical orientation, could significantly enhance the k in the oriented direction while sacrificing the performance in the perpendicular one; therefore, these strategies fail to reach simultaneously high thermal conductivities in 3D for the polymer/filler composites. [5,[39][40][41] Although recent studies reported a radially structured method to align fillers both in out-of-plane and radial directions, radially aligned polymer/filler composites perform isotropic thermal conductivities of less than 6 W m −1 K −1 due to restricted filler additions. [42][43][44] Fortunately, attributed to the hierarchical thermal-transport highways including extended macromolecular chain configurations in the PBO fiber, the tightly arranged fibrous spiral structure in the twisted PBO bunch, and the weaving structure in the epoxy matrix, our epoxy/PBO bulk materials, through a scalable fabrication approach, perform exceedingly high thermal conductivities both in the inplane and out-of-plane directions, successfully extending the 1D thermoconductive nature of PBO fibers to the 3D space within the bulk material.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the research core in the subsequent stage will be on lowering the contact thermal resistance, which may be achieved by the following routes: (1) construction of vertically aligned, covalently bonded graphene architectures for the fabrication of highly thermally conductive composites with extremely low filler contents, where the low graphene loading results in a lower increase in compressive modulus, thereby improving the gap-filling capacity of TIMs; or (2) completely removing the polymers (positive Poisson's ratio materials) and creating negative Poisson's ratio TIMs for compressibility optimization via the rational design of 3D graphene structures; (3) developing surface modification strategies of TIMs via employing highly thermally conductive, soft and malleable martials as the buffer layers to increase the contact area between the heater/TIM/heat sink. Except for these, TIMs should even be endowed with more novel properties, such as self-healing capacity and adhesion ability [122][123][124], to improve their usability in practical applications, and the complexity of the fabricating process as well as the cost of preparation are also important in determining whether they can truly realize industrialization. Overall, only taking into account all the factors can solve the problems that are impeding the practical widespread use of graphene-based TIMs.…”
Section: Conclusion and Prospectmentioning
confidence: 99%